Hubungan Indeks Massa Tubuh dengan Kekuatan Genggam Tangan pada Lansia di PSTW Sabai Nan Aluih - Siregar, Fatia Putri Barokah; Irawati, Lili; MYH, Etriyel; Fasrini, Ulya Uti; Wahid, Irza; Abdiana, Abdiana (Jurnal Biomedika dan Kesehatan, 2024)
Background The aging process results in physiological changes in the body, such as decreased muscle strength and impaired balance, so that the risk of falls, injury and dependency increases in the elderly. Changes in the nutritional status of the elderly who tend to be predominantly underweight also occur due to the aging process and have an impact on the muscle strength of the elderly in the long term. This study aims to determine the relationship between BMI and hand grip strength in the elderly at PSTW Sabai Nan Aluih Sicincin. Methods This study is an analytical and secondary research with a cross-sectional design, involving 62 elderly individuals from PSTW Sabai Nan Aluih Sicincin as the population. All population members meeting the inclusion criteria and excluding outliers were considered as the research sample. The inclusion criteria encompassed complete data such as BMI, handgrip strength, age, weight, knee height, and gender. Two outlier samples were excluded based on the exclusion criteria. Bivariate data analysis utilized the Chi-square statistical test. Results The research findings indicate that most elderly women at PSTW Sabai Nan Aluih Sicincin have normal to overweight BMI, while elderly men have underweight BMI. Elderly women at PSTW Sabai Nan Aluih Sicincin exhibit abnormal handgrip strength, whereas elderly men have normal handgrip strength. Furthermore, there is no significant relationship (p=0.676) between BMI and handgrip strength values among the elderly at PSTW Sabai Nan Aluih Sicincin. Conclusions This study concluded that there was no significant relationship between BMI and hand grip strength scores in the elderly at PSTW Sabai Nan Aluih Sicincin.